Microgrid management system based on a multi-agent approach: An office building pilot - Gomes, Luis (2021)
Microgrids bring advantages to end-users and to the smart grid environment. However, adequate management software, enabling bringing to the field new energy management concepts, is not available yet. Small, single-tasked, software is usually proposed and tested while a clear overall system architecture for microgrid management required to take full advantage of the microgrids’ potential. Previous publications usually focus on energy-related problems and do not provide an efficient and viable solution for players’ representation and microgrid operation. This paper proposes a complete architecture for a microgrid management system based on a multi-agent approach – µGIM – allowing the easy implementation of different energy strategies. The µGIM agents can independently manage local resources while able to collaborate and/or compete with other agents. Designed to run in single-board computers, µGIM agents are light-weighted and easily deployed in buildings. To demonstrate these capabilities, the paper details and presents a microgrid deployment using µGIM solution.